Determinan Kepatuhan Berzakat di Masa Pandemi dengan Tingkat Pemahaman sebagai variabel Intervening - Mukti Prasaja; Nunung Susilaningsih; Riski Novitasari; Nabila Andriani; Ferdy Yunanto (Jurnal Ilmiah Ekonomi Islam, 2022)
The potential of zakat in Indonesia is still much unrealized, but the increase in zakat acquisition from year to year needs to be appreciated. Moreover, at the end of 2019 precisely in December there was an outbreak of covid 19 in China. This increase is certainly caused by many factors ranging from the performance of Zakat Institutions and increased public understanding of the importance and obligations of Zakat as a Muslim. This study used zakat service quality variables, altruism as independent variables, the level of understanding for intervening variables and the compliance rate of its dependent variables. The research method uses questionnaires with data analysis using the path method. The results altruism had no influence on the compliance of paying zakat while the service variable of zakat institutions had an influence on the compliance of paying zakat. Meanwhile, the level of understanding has an influence on the compliance of paying zakat. For indirect influence of intervening variables indicate for altruism to zakat compliance the value is higher when passing the level of understanding whereas the service quality variable is higher value when directly to the level of compliance rather than having to go through the level of understanding